Analysis of Customer Behavior in Online Retail Marketplace Using Hadoop (International Journal of Innovative Research in Computer Science & Technology, 2017)
To provide a modernized technology foundation for transforming the retail experience,  retail CIOs and IT leaders need to support the "seven  Cs" of customer interaction: connected, continuous,  convenient, contiguous, consistent, collaborative and  customized [1]. The biggest differentiator of any online  marketplace is how well the store understands its  customer and provides the personalized experiences.  Retailers interact with customers across multiple  channels, yet customer interaction and purchase data  is often isolated in data siloes. This paper attempts to  identify the use cases to accurately correlate eventual  customer purchases with marketing campaigns and  online browsing behavior. The data used in this  analysis was collected from a start- up online retailer  in India.
Keywords: Adaptive Retail; Big data; Hadoop; RDBMS